Playing Against Players : Dangerous Boundaries of the "Magic Circle" : Preface - Serada, Alesha (European Humanities University, 2022)
This is the introduction to the collection of academic papers united by the topic “Playful violence and ludic control”. The overarching goal is to critically investigate the dark side of the video game medium (without getting scared by what we see). To layout new paths and establish alternative perspectives on the canon of so-called ‘game studies’, we aspired to gather ideas of both young and established scholars in one collective publication. Before moving on to our modest contribution, we feel obliged to provide a summary of key topics and questions that video games pose to their researchers. Which ones remain acutely relevant today? On the other hand, which roads have been already taken, and which quests have been already completed? Finally, what are the implicit rules of the academic field that we dare to enter, and can we suggest any original ways to disrupt these rules?
ИГРЫ ПРОТИВ ИГРОКОВ : ОПАСНЫЕ ГРАНИЦЫ «МАГИЧЕСКОГО КРУГА» : ПРЕДИСЛОВИЕ
Keywords: game ethics; ludic violence; transgression; militainment; media effects; fi=Viestintätieteet|en=Communication Studies|